Unpaid work, capital and coercion. (1st April 2012) - Norene Pupo; Ann Duffy
Abstract : Over the past several decades, household work has generated a dramatic outflow of research and theory on unpaid work. Here, the authors (who shared equally in the writing of this paper) examine multiple forms of unpaid work and propose that in the contemporary capitalist economy the key dimensions of unpaid work are: first, that it is not compensated in terms of direct payments by capital; second, that elsewhere in the economy the same activities are paid; and, lastly, that participation in unpaid work is directly related to socially constructed power relations. Within this framework, they point out the complex and dynamic interplay between unpaid work and patterns of social inequality. In conclusion, it is proposed that approaching unpaid work, and in particular domestic labour, in this broader context and in terms of more nuanced treatments of power provides a fuller understanding of the issues and suggests that unpaid work may be in the midst of dramatic expansion. The implications of this growth for individuals and societies around the globe warrant researchers' attention.